Effect of lift force and hydrodynamic torque on fluidisation of non-spherical particles. (23rd February 2019) - Mema, Ivan; Mahajan, Vinay V.; Fitzgerald, Barry W.; Padding, Johan T.
Graphical abstract: Highlights: CFD-DEM simulations of spherocylindrical particles in a fluidised bed. Explore the effect of varying hydrodynamic force conditions. Lift and torque correlations derived from recent DNS simulations are used. Lift has considerable influence on the velocity of particles parallel to fluid flow. Inclusion of hydrodynamic torque greatly affects preferred orientation of particles. Abstract: The aim of many industrial processes is to manipulate solid particle aggregates within gas suspensions. Prime examples of such processes include fluidised bed reactors, cyclone separators, and dust collectors. In recent years, fluidised bed reactors have been used in the gasification of biomass particles. When fluidised, these particles are subject to various hydrodynamic forces such as drag, lift and torque due to interactions with the fluid. Computational approaches, which can be used to replicate laboratory and industrial scale processes, offer a crucial method for the study of reactor design and for the formulation of optimal operating procedures. Until now, many computer models have assumed particles to be spherical whereas, in reality, biomass feedstocks typically consist of non-spherical particles. While lift and torque are of minimal importance for spherical particles, non-spherical particles experience varying lift force and torque conditions, depending on particle orientation relative to the direction of the fluid velocity. In this study, we present a numerical investigation on the effect of different lift force and torque correlations on fluidised spherocylindrical particles. We find that lift force has a significant influence on particle velocities parallel to the direction of gravity. On the other hand, particle orientation is dependent on hydrodynamic torque. Results from this numerical study provide new insight with regards to the dynamics of non-spherical particles that can be of paramount importance for industrial processes involving non-spherical particles.